Burdens of history : British feminists, Indian women, and imperial culture, 1865-1915 - Burton, Antoinette M., 1961- (University of North Carolina Press, 1994)
In this study of British middle-class feminism in the late nineteenth and early twentieth centuries, Antoinette Burton explores an important but neglected historical dimension of the relationship between feminism and imperialism. Demonstrating how feminists in the United Kingdom appropriated imperial ideology and rhetoric to justify their own right to equality, she reveals a variety of feminisms grounded in notions of moral and racial superiority.